Pengaruh Motivasi Intrinsik, Motivasi Ekstrinsik, Budaya Organisasi, dan Komitmen Organisasional Terhadap Kinerja Pegawai - Afdi Tria Putra; Jajuk Herawati; Ignatius Soni Kurniawan (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine the effect of intrinsic motivation, extrinsic motivation, organizational culture, and organizational commitment on employee performance. The population of this research is the employees of Kecamatan Jangkat, Kabupaten Merangin, Jambi. Data was taken on all employees or 33 employees by the census method. Data collection was carried out by survey using a questionnaire instrument. The research method used in this study is a quantitative method with data analyzed by multiple linear regression analysis. The results showed that intrinsic motivation had no significant effect on employee performance. Extrinsic motivation has no significant effect on employee performance. Organizational culture also has no significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance. Strengthening organizational commitment becomes an implication if the leader intends to encourage employee performance. Keywords: organizational culture; employee performance; organizational commitment; extrinsic motivation; intrinsic motivation.